4-arms poly (caprolactone) star-shaped polymer for drug delivery application: synthesis and characterization - Ahmad Shariff, Siti Hajar; Ismail, Mohamad Wafiuddin (2020)
Star-shaped polymers have vast potential in bioapplication due to their architecture. In this study, 4 -arm star-shaped of poly(ԑ-caprolactone) (4s PCL) with -OH terminal and average molecular weight (Mn) of 5, 10, and 15 kDa, were synthesized via ring opening polymerization, (ROP) of ԑ-caprolactone (ԑ-CL) using a symmetric pentaerythritol (PET) as the core. Different molecular weight were obtained by using different ratio of ԑ-CL and PET in the presence of catalyst, stannous octoate (Sn(Oct)2). The FTIR spectra showed the presence of bands of methylene group of polymer repeating chain which confirm ROP of the ԑ-caprolactone. The molecular weight (Mn) determined from 1H NMR analysis showed that all 4s PCLs have approximately the same molecular weight as the theoretical values. TGA and DSC analysis showed a single step degradation for all 4s PCL and the crystallization melting point of the polymers within the range of melting point of PCL.